Isolasi Bakteri Pelarut Fosfat (Asal Rizosfer Tanaman Cabe) dan Uji Kemampuannya Mengendalikan Fusarium - Aura Khairani, Fidia (Universitas Cokroaminoto Palopo, 2025)
This study aims to isolate phosphate-solubilizing bacteria (PSB) from the rhizosphere of chili plants and test their ability to control Fusarium, a major pathogen causing wilt in chili plants. Isolation was conducted using the dual culture method on PDA and PDA+NA media. Results showed that PSB could solubilize inorganic phosphate and significantly inhibit Fusarium growth. PDA+NA media provided the best results for PSB growth, while PDA was optimal for Fusarium. The study concludes that PSB has potential as an eco-friendly biological agent to mitigate Fusarium infection in chili plants